Periorbital rejuvenation with fractional 1,550-nm ytterbium/erbium fiber laser and variable square pulse 2,940-nm erbium:YAG laser in Asians: A comparison study - Penpun Wattanakrai (2018)
BACKGROUND: Ablative and fractional lasers are used for periorbital rejuvenation, with different downtime, side effects, and efficacy. OBJECTIVES: To compare effects of fractional 1,550-nm ytterbium- and erbium-doped (Yb/Er) fiber laser and variable square pulse (VSP) 2,940-nm erbium-doped yttrium aluminum garnet (Er:YAG) laser treatment for periorbital wrinkles. MATERIALS AND METHODS: This side-by-side comparison study randomized 22 women with mild to moderate periorbital rhytides to receive three treatments with fractional 1,550-nm Yb/Er fiber laser or 2,940-nm Er:YAG laser treatment on either side at 4-week intervals. A video camera was used for objective assessment of wrinkles. Standardized photographs, patient satisfaction, side effects, and pain score were recorded. RESULTS: Twenty subjects completed the study. The median change in wrinkle measurement 3 months after laser treatments from baseline of the fractional Yb/Er fiber laser side was -3.03 versus -3.09 on the VSP Er:YAG side (p = .63, Wilcoxon signed-rank test). There was no significant difference in degree of wrinkle improvement analyzed according to global assessment between the sides (p = .25, Wilcoxon signed-rank test). Less downtime correlated with greater patient satisfaction of the fractional laser treatment . Two subjects experienced hyperpigmentation. CONCLUSION: Fractional Yb/Er fiber and VSP Er:YAG lasers are effective in improving periorbital wrinkles in Asians, with minimal side effects. © 2012 by the American Society for Dermatologic Surgery, Inc. Published by Wiley Periodicals, Inc.